Detecting pneumonia from chest X-rays using deep learning based neural networks: an hybrid approach - Suta Siva Nishanth, Konjeti Naga Venkata Pavana; Basha, Syed Althaf; Srikanth, Vissamsetty; Narendra, Kommi Purna; Rachapudi, Venubabu (Institute of Advanced Engineering and Science, 2025)
Pneumonia a disease which occurs when the alveoli (air sacs) in the lings fill with fluidlike substance it can be due to infectious agents like virus, bacteria especially in an environment with contaminated air is often considered as lethal disease because the deaths associated with is high. There are several factors which contribute to this disease like age as their immune systems are not fully developed making it easier to get attacked by infections, chronic health conditions like asthma or weak immune systems may worsen the situation. Machine learning (ML) algorithms have tend to perform better while images are given, however compared to them deep learning (DL) algorithms have shown good promising results especially when images are given as an input this is because they have upper hand in identifying key features and loss optimization makes them best suited for this tasks. The significance of this research is to make an extensive review on the pneumonia and early detecting pneumonia by utilizing DL based neural networks.